2019
DOI: 10.1002/pds.4700
|View full text |Cite
|
Sign up to set email alerts
|

Validating registry data on statins prescriptions by blood measurements

Abstract: Purpose To validate prescription registry data as a measurement of adherence to statins through a direct method using assays for selected statins in serial blood samples collected from two prospective cohorts of Danish colorectal cancer patients. Methods We linked information on statin prescriptions from the Aarhus University Prescription Database with the cancer cohorts from Aalborg University Hospital. For statin‐prescribed patients, we calculated a prescription window covering the anticipated duration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The major strengths of our study are its unselected Danish source population (which virtually eliminates the possibility of selection bias) 31 and its use of high-quality registry data on simvastatin exposure, 19,32 vital status, 16,17 and breast tumor characteristics, treatment, and recurrence. 33,34 We expect little to no residual confounding, as germline genetic status is encoded at conception, and thus cannot be acted upon causally by demographic, behavioral, or clinical factors that may influence recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
“…The major strengths of our study are its unselected Danish source population (which virtually eliminates the possibility of selection bias) 31 and its use of high-quality registry data on simvastatin exposure, 19,32 vital status, 16,17 and breast tumor characteristics, treatment, and recurrence. 33,34 We expect little to no residual confounding, as germline genetic status is encoded at conception, and thus cannot be acted upon causally by demographic, behavioral, or clinical factors that may influence recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in the Danish setting has previously found high adherence to statins. 36 Logistic regression models were not suitable for comparisons with XGBoost when the models' complexity increased. This was mainly due to 2 reasons.…”
Section: Limitationsmentioning
confidence: 99%
“…The laboratory test will also have to have demonstrated accuracy for identifying the measure of interest. One group validated the use of the Danish prescription registry as a measurement of adherence to statins via serially collected blood samples to detect statins and their metabolites and found that the electronic algorithm performed very well, implying such an approach will be appropriate for most studies that examine statin use 15 Exposure: To identify individuals treated with intravenous immunoglobulin in the inpatient setting, we use inpatient medical record data that documented the administration of the product of interest to the person of interest. Outcome: To identify intussusception as an outcome among US children who received rotavirus vaccine, we identify potential cases via an electronic algorithm based on diagnosis or procedure codes captured in claims data and only include in the analysis those cases that are confirmed by manual record review with clinician adjudication 16 .…”
Section: The Frameworkmentioning
confidence: 99%